Serological Evidence of Chikungunya Virus among Acute Febrile Patients in Southern Mozambique. - Eduardo Samo Gudo; Gabriela Pinto; Sirkka Vene; Arcildo Mandlaze; Argentina Felisbela Muianga; Julie Cliff; Kerstin Falk (Public Library of Science (PLoS), 2015)
BACKGROUND:In the last two decades, chikungunya virus (CHIKV) has rapidly expanded to several geographical areas, causing frequent outbreaks in sub-Saharan Africa, South East Asia, South America, and Europe. Therefore, the disease remains heavily neglected in Mozambique, and no recent study has been conducted. METHODS:Between January and September 2013, acute febrile patients with no other evident cause of fever and attending a health center in a suburban area of Maputo city, Mozambique, were consecutively invited to participate. Paired acute and convalescent serum samples were requested from each participant. Convalescent samples were initially screened for anti-CHIKV IgG using a commercial indirect immunofluorescence test, and if positive, the corresponding acute sample was screened using the same test. RESULTS:Four hundred patients were enrolled. The median age of study participants was 26 years (IQR: 21-33 years) and 57.5% (224/391) were female. Paired blood samples were obtained from 209 patients, of which 26.4% (55/208) were presented anti-CHIKV IgG antibodies in the convalescent sample. Seroconversion or a four-fold titer rise was confirmed in 9 (4.3%) patients. CONCLUSION:The results of this study strongly suggest that CHIKV is circulating in southern Mozambique. We recommend that CHIKV should be considered in the differential diagnosis of acute febrile illness in Mozambique and that systematic surveillance for CHIKV should be implemented.